Kinerja Karyawan melalui Lingkungan Kerja dan Kompetensi Dinas Sosial kabupaten Bangkalan - Syarifah, Nurus; Wispandono, Mochammad (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
Nurus Syarifah, The Effect of Work Environment and Competence on Employee Performance at the Dinas Sosial Kabupaten Bangkalan Service Office.Under the guidance of Dr.RM. Mochammad Wispandono, S.E., MS.This study aims to find out whether there is an Effect of Work Environment and Competence on Employee Performance in the Dinas Sosial Kabupaten Bangkalan Office. The approach used in this study was quantitative research by takibf the number of research samples using a simple random sampling method with a total research sample of 71 employees. The method used is multiple linear regression analysis. The data collection techniques used are interviews, questionnaires and documentation. The data analysis techniques used are validity and reliability tests, classical assumption tests, regression analysis and hypothesis tests.Based on the research that has been carried out, the results were obtained that (1) partially the variable of the work environment have a positive and significant effect on performance with the value oft count compared to the t table is 5.353 1.6 6757 and a significance level of 0.000 0.05. (2) partially the competence variable has a positive and significant effect on performance with the value of count compared to the t table is 7.729 1.66757 and the significance level is 0.000 0.05. (3) simultaneously the independent variables (work environment, competence) affect the dependent variable (employee performance) with the simultaneous test significance level being 0.000 0.05 and the F-count value is greater than the F-table which is 38.443 3.13. (4) the competency variable has a dominant effect on performance having a higher beta value of 0.651Keywords: Work Environment, Competence, Employee Performance.